Towards Agricultural Digitalization: Does Higher Agricultural Education Supply Students with Relevant Competencies? - Chrysanthi Charatsari; Anastasios Michailidis; Evagelos D. Lioutas; Thomas Bournaris; Efstratios Loizou; Aikaterini Paltaki; Dimitra Lazaridou (Proceedings)
Agricultural digitalization is gaining momentum, urging a transition from process-driven to technology-enhanced and data-driven agriculture. To support such a transition and help farmers derive benefits from digital technologies, also avoiding the potential threats associated with digitalization, future advisors need a variety of competencies, ranging from pure technocentric skills to more complex capabilities, such as impact forecasting and transition facilitation. Do Greek students who study to become advisors have these competencies? In this study, we attempted to answer this question following a quantitative approach. The results indicate that participants possess low levels in all the examined sets of competencies and, as a result, have limited overall competency in dealing with digital agriculture. These findings suggest the need for agricultural universities to reset competence-related targets and design strategies to supply future farm advisors with the competencies needed to act as facilitators of agricultural digitalization.